Afrikaanse krijgsheren, versterking of ondermijning van het historisch kapitalisme? - Vervaet, Stephanie (Afrika Focus, 2006)
With the end of the Cold War, global economic and political changes made African leaders rearrange their patrimonial politics towards warlord strategies. The aim of this paper is to find out what the influences are of these evolutions for the capitalist world-system. Is warlordism nothing more than a way of surviving for third world countries or does it affect historical capitalism? Is the upsurge of warlords an expression of the crisis of the modem world-economy or is it on the contrary capitalism pur sang? This paper does not provide a conclusive answer to these questions. It is only an attempt to consider warlords in the world-system from diverse perspectives. Key Words: Capitalist World-System, African Warlordism, State-Building, Mafia, Anti-Systemic Movement, Colonialism